Experimental and analytical investigations on a large floor truss pinned connection. Issue 7 (July 2017) - Ding, Dayi; Wang, Meng; Wang, Yuanqing; Pan, Bin; Shi, Yongjiu
The pinned connection method was used to connect the large-span floor truss to the steel column in Zoucheng International Conference Center project, which played a quite important role to achieve the in-plane rotation and transfer heavy loads directly. Four specimens were tested experimentally to investigate the monotonic and cyclic behavior of this connection method, including two independent pinned connections and two assembled truss connections. The load–displacement curves, deformation development, failure mode, ductility, and energy dissipation capacity were discussed in detail. Besides, the nonlinear multi-scale finite element models of the pinned and truss connections were established. The numerical simulations not only captured the global behavior and local limit states observed in tests but also revealed valuable new information that could not be directly obtained from the tests. The experimental and numerical results showed that both the pinned and truss connections had good ductility, load transfer ability, and ideal rotation capacity with large safety margin, indicating these constructions could be used as references for similar projects.